PENGARUH CAR, LDR DAN BOPO TERHADAP ROA PERUSAHAAN PERBANKAN KONVENSIONAL DI BEI - HUTAGALUNG, AGUS BOICE (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine the effect of Capital Adequacy Ratio, Loan to Deposit Ratio, and BOPO simultaneously and partially on Return On Assets of Conventional Banking Companies in the Indonesia Stock Exchange. The population in this study were 42 conventional banking companies listed on the Indonesia Stock Exchange. Sampling was carried out by purposive sampling method with the aim of obtaining samples in accordance with the research objectives and from the number of samples taken as many as 11 companies. The analytical method used in this study is panel data regression analysis.The results of this study indicate that during the period 2012-2016 (1) simultaneously CAR, LDR and BOPO had a significant effect on ROA in conventional banking companies listed on the IDX, (2) CAR partially had no significant effect on ROA, (3) LDR partially no significant effect on ROA, (4) BOPO partially has a significant effect on ROA of conventional banking companies on the Indonesia Stock Exchange.